Root Metabolite Differences in Two Maize Varieties Under Lead (Pb) Stress - Zhang, Hanqian; Qin, Yuying; Huang, Kai; Zhan, Fangdong; Li, Ru; Chen, Jianjun (Frontiers in Plant Science, 2021)
To assess root metabolic differences of maize varieties in their response to lead (Pb) stress, the lead-tolerant variety Huidan No. 4 and the lead-sensitive variety Ludan No. 8 were tested under Pb-free and Pb-stressed conditions. Changes in metabolites were measured using ultra-performance liquid chromatography-mass spectrometry. Pb stress changed the levels of the amino acids proline, glutamine, lysine, and arginine in both varieties, whereas glutamate and phenylalanine levels changed only in Huidan No. 4. Pb stress altered cystine, valine, methionine, and tryptophan levels only in Ludan No. 8. Therefore, the synthesis and decomposition of amino acids may affect the response of maize to Pb stress. The degree of change in differential metabolites for Huidan No. 4 was greater than that for Ludan No. 8. In cell wall subcellular components, increases in superoxide dismutase (SOD), peroxidases (POD), and Pb concentrations were greater in Huidan No. 4 than in Ludan No. 8. Therefore, the greater Pb tolerance of Huidan No. 4 could be due to better sequestration of Pb in cell walls and more effective removal of reactive oxygen species (ROS) from the plant. The levels of certain metabolites only increased in Ludan No. 8, indicating that Pb-sensitive varieties may use different metabolic pathways to cope with Pb stress. Both varieties showed increased levels of some metabolites related to antioxidant protection and osmotic regulation. This study provides an understanding of maize Pb tolerance mechanisms and a basis for further development of tools for use in maize breeding.